Mermaid Becomings: Transition and Self-Care in a Former Religious Woman’s Embodied Relation to Nature - Rantala, Teija; Kontturi, Katve-Kaisa (Matter: Journal of New Materialist Research, 2026)
This article considers how transition, in other words, the process of becoming, self-care and an embod-ied relation to nature interweave in the self-expression of a woman who used to belong to a procrea-tional, conservative religious movement, the Conservative Laestadians. In this article, we focus on herself-portrait andspoken narrative, which were created in an interview organised for women in transition from the religious movement. To study the woman’s embodied relation to nature, we turn to the feminist and posthuman philosophies of Luce Irigaray and Michael Marder as well as to the feminist and religiousimageries ofwomen.Reading the hand-drawn self-portrait as a mermaidand related spoken narrativewith Irigaray’s and Marder’s ‘mattering’–together with the vivid natural elements of water, earth and air–enables us to illustrate the woman’s embodied relation to nature as part of her self-care during the transition.